Hepatoprotective Potential of Tephrosia purpurea in Thioacetamide-Induced Hepatotoxicity in Rats: Hepatoprotective Potential of Tephrosia purpurea in Thioacetamide-Induced Hepatotoxicity in Rats - Desai, Prashant Kumar (International Journal of Pharmaceutical & Biological Archive, 2020)
Background: Hepatotoxicity ultimately leads to liver failure. Conventional treatment options for hepatotoxicity are limited and not safe. Aim: The present work has been designed to evaluate the hepatoprotective effects of ethanolic extract of the root of Tephrosia purpurea (Linn.) against thioacetamide-induced hepatotoxicity in experimental Wistar albino rats. Materials and Methods: The plant roots, T. purpurea, were collected from the local area of Jodhpur, Rajasthan, and verification was done by Botanical Survey of India (BSI), Jodhpur, Rajasthan, and a herbarium specimen was deposited in BSI with No. LMC/PM/PD-001. All other reagents and chemicals were of suitable analytical grade and were used as received. Results: On the basis of statistical analysis, both the doses (200 and 400 mg/kg b.wt) of the ethanolic extract of T. purpurea root shown significant hepatoprotective activity compare to negative control. The dose of 400 mg/kg b.wt showed better reduction in serum enzyme level compare to 200 mg/kg b.wt dose of the ethanolic extract of T. purpurea root. Results were determined by one-way analysis of variance (ANOVA non-parametric) followed by Dunnett’s test with P < 0.01 considered statistically significant. Conclusion: Based on the results obtained, it may be concluded that the ethanolic extract of T. purpurea root has a significant protective effect on liver injuries.